POLA PERILAKU "ALONE TOGETHER" MAHASISWA DI UNIVERSITAS NEGERI SURABAYA - Rahman, Muhammad Faisal Aditya; Dewi, S.Sos., M.Med.Kom., Putri Aisyiyah Rachma (The Commercium, 2023)
This research aims to analyze the "Alone Together" behavior patterns exhibited by students at Universitas Negeri Surabaya. The concept of "Alone Together" refers to a situation where individuals are physically together but remain focused on online interactions and lack of direct social engagement. The study adopts a qualitative approach with in-depth interviews and participatory observation techniques to collect data. The research findings reveal that students at Universitas Negeri Surabaya tend to exhibit "Alone Together" behavior patterns in various situations. They prefer communicating through digital platforms such as social media, instant messaging, and email rather than engaging in face-to-face interactions. Even when present in the same physical space, students tend to be more engaged with their electronic devices than directly interacting with their peers. Several factors contributing to these behavior patterns include technological advancements, the convenience of online communication, and a tendency to prioritize individual activities over social interactions. Additionally, the "Alone Together" behavior may also be influenced by high levels of technology dependence and concerns about the lack of privacy in face-to-face interactions.